Textiloma Mimicking a Recurrent High-Grade Astrocytoma: A Case Report - Jaramillo-Jiménez, Esteban; Gupta, Manu; Snipes, George; Cheek, Brennen S.; Michael, Christopher B.; Navarro-Montoya, Ana M.; Gómez-Escobar, Tatiana; Jiménez-Villegas, Juliana; Rodríguez-Márquez, Iader; Melguizo-Gavilanes, Isaac (Journal of Neurological Surgery Reports, 2020)
Introduction Textiloma (Txm) is a nonmedical term that has been given to foreign body-related inflammatory pseudotumor arising from retained nonabsorbable cotton matrix that is either inadvertently or deliberately left behind during surgery, which may trigger an inflammatory reaction. This report describes a case of Txm mimicking a recurrent high-grade astrocytoma.Case Report We, here, present the case of a 69-year-old female with a 6-month history of progressive left-sided weakness. Neuroimaging studies revealed a large nonenhancing mass in the right frontoparietal lobe. Pathology reported a World Health Organization tumor classification grade II, diffuse astrocytoma. After surgical intervention, external beam radiation was given to the remaining areas of residual tumor. Routine magnetic resonance imaging (MRI) revealed a nodular area of contrast enhancement in the dorsal and inferior margin of the biopsy tract, growing between interval scans, and perfusion-weighted imaging parameters were elevated being clinically asymptomatic. She underwent a complete resection of this area of interest and pathology returned as a Txm with Surgicel fibers.Conclusion After treatment of a neoplasm, if unexpected clinical or imaging evidence of recurrence is present, a foreign body reaction to hemostatic material used during the initial surgery should be included in the differential diagnosis.
Keywords: foreign body; astrocytoma; neoplasm recurrence; local; textiloma